Pengaruh Pembelajaran Berbasis Proyek Terhadap Perkembangan Sosial Emosional Anak Usia 5-6 Tahun Di Tk Riyadlussolihin - Rina Marlina; Ajeng Teni Nur Afriliani; Tita Puspita (Institut Madani Nusantara, 2024)
Social emotional development is a very important development for a child considering that this development will determine the child's ability to adapt to their environment later. The problem that often occurs today is that many children have problems with social emotional development, for that reason a method is needed that can stimulate it. One method that can stimulate this development is the project learning method. The purpose of this study was to see the effect of the project method on the social emotional development of early childhood in Riyadlussolihin Kindergarten, Takokak District. The method used in this study was Pre-Experiment One-Group Pretest - Posttest Design, the research subjects were 20 children aged 5-6 years in class B. The place that became the location of the study was Riyadlussolihin Kindergarten, Takokak District. The data collection techniques used were observation and documentation. The results of the study indicate a significant effect of project-based learning on the social-emotional development of children aged 5-6 years, as seen from the simple linear regression test value, with a significance value of 0.000, less than 0.05, and the influence of project-based learning variables on children's social-emotional development. This means that project-based learning has an effect on the social-emotional development of children aged 5-6 years at Riyadlussolihin Takokak Kindergarten.